Perinatal exposure to a glyphosate-based herbicide causes dysregulation of dynorphins and an increase of neural precursor cells in the brain of adult male rats. (September 2021) - Cattani, Daiane; Struyf, Nona; Steffensen, Vivien; Bergquist, Jonas; Zamoner, Ariane; Brittebo, Eva; Andersson, Malin
Abstract: Glyphosate, the most used herbicide worldwide, has been suggested to induce neurotoxicity and behavioral changes in rats after developmental exposure. Studies of human glyphosate intoxication have reported adverse effects on the nervous system, particularly in substantia nigra (SN). Here we used matrix-assisted laser desorption ionization (MALDI) imaging mass spectrometry (IMS) to study persistent changes in peptide expression in the SN of 90-day-old adult male Wistar rats. The animals were perinatally exposed to 3 % GBH (glyphosate-based herbicide) in drinking water (corresponding to 0.36 % of glyphosate) starting at gestational day 5 and continued up to postnatal day 15 (PND15). Peptides are present in the central nervous system before birth and play a critical role in the development and survival of neurons, therefore, observed neuropeptide changes could provide better understanding of the GBH-induced long term effects on SN. The results revealed 188 significantly altered mass peaks in SN of animals perinatally exposed to GBH. A significant reduction of the peak intensity (P < 0.05) of several peptides from the opioid-related dynorphin family such as dynorphin B (57 %), alpha-neoendorphin (50 %), and its endogenous metabolite des-tyrosine alpha-neoendorphin (39 %) was detected in the GBH group. Immunohistochemical analysis confirmed a decreased dynorphin expression and showed a reduction of the total area of dynorphin immunoreactive fibers in the SN of the GBH group. In addition, a small reduction of dynorphin immunoreactivity associated with non-neuronal cells was seen in the hilus of the hippocampal dentate gyrus. Perinatal exposure to GBH also induced an increase in the number of nestin-positive cells in the subgranular zone of the dentate gyrus. In conclusion, the results demonstrate long-term changes in the adult male rat SN and hippocampus following a perinatal GBH exposure suggesting that this glyphosate-based formulation may perturb critical neurodevelopmental processes.